Fifty Most Cited Articles for Femoroacetabular Impingement and Hip Arthroscopy - Lee, Simon; Shin, Jason; Haro, Marc; Khair, Michael; Riboh, Jonathan C.; Kuhns, Benjamin D.; Bush-Joseph, Charles A.; Nho, Shane J. (Frontiers in Surgery, 2015)
Growing awareness of femoroacetabular impingement (FAI) and recent innovations in management has resulted in hip arthroscopy becoming one of the fastest-growing orthopaedic subspecialties. The purpose of this study was to identify the 50 most cited articles related to the topic of FAI and hip arthroscopy and to analyze their characteristics.The overall number of citations within these articles ranged from 99 to 820. Citation density ranged from 4.41 to 74.55. Seven countries produced these articles with the majority attributed to the United States (n=26) and Switzerland (n=18). Clinical studies made up more than half of the top articles (n=27). The JBJS level of evidence most commonly encountered was level IV (n=24) while the remaining articles were level III (n=3). No randomized controlled trials or non-randomized controlled trials were encountered in this search. The level of evidence was not significantly correlated with the overall number of citations, publication year, or citation density. The current top 50 list provides orthopaedic surgeons interested in hip arthroscopy with anup-to-date core list of the most cited articles in the scientific literature and represents a foundation to use to develop their knowledge regarding hip arthroscopy and FAI.